Overcoming learning obstacles in cylinder and cone volume: A didactic design research approach - Titin Suryani; Jamilah; Reni Astuti (Jurnal Elemen, 2025)
Many students encounter learning obstacles when understanding the volume of cylinders and cones; however, few studies have explicitly integrated these obstacles into didactic design. This study aimed to develop a didactic design to address specific learning obstacles in understanding the volume of cylinders and cones. Using a Didactic Design Research (DDR) approach grounded in Brousseau’s Theory of Didactic Situations, the study involved 28 seventh-grade students and a mathematics teacher from a junior high school in Pontianak, selected through purposive sampling. Data were collected through observations, diagnostic tests, and interviews and then analyzed qualitatively using interpretative and critical techniques. The didactic design consisted of four didactic situations: action, formulation, validation, and institutionalization, implemented in classroom practice. The institutional phase revealed several limitations, particularly a lack of sufficient scaffolding and inadequate visual support for students’ spatial reasoning. The findings indicate that addressing epistemological obstacles, such as misconceptions regarding the interpretation of height and base area in three-dimensional solids, can enhance students’ conceptual understanding. The study suggests that integrating learning obstacle analysis into didactic design helps refine future implementations to better anticipate students’ cognitive development.